2008
DOI: 10.1556/avet.56.2008.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Plasma parathyroid hormone-related peptide and bone metabolism in periparturient dairy cows

Abstract: The first weeks of lactation in dairy cows are characterised by elevated bone resorption. The connection between lactation and bone metabolism is still much discussed. In this work, changes in the concentration of plasma parathyroid hormone-related peptide (PTHrP) and markers of bone metabolism were studied in Holstein cows and heifers in the dry period and early lactation to determine the role of PTHrP in the relationship between the rate of bone remodelling and the onset of lactation in dairy cows. Blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…e present investigations found that the bone formation biomarkers (OC and b-ALP) did not change significantly during the periparturient period of the goats. is is in agreement with data in dairy cows, where significant changes in the activity of b-ALP in the blood serum were not established during late pregnancy and early lactation [24]. On the other hand, the activity of bone formation b-ALP in the serum of mares was lower in late pregnancy than in early lactation [12].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…e present investigations found that the bone formation biomarkers (OC and b-ALP) did not change significantly during the periparturient period of the goats. is is in agreement with data in dairy cows, where significant changes in the activity of b-ALP in the blood serum were not established during late pregnancy and early lactation [24]. On the other hand, the activity of bone formation b-ALP in the serum of mares was lower in late pregnancy than in early lactation [12].…”
Section: Resultssupporting
confidence: 92%
“…Veterinary Medicine International estradiol were reported to influence the rate of bone turnover [12,22,24]. Filipovic et al [12] suggested that high concentrations of estradiol in the blood during late pregnancy could cause a decrease in the number of osteoblasts because estrogens suppress the self-renewal of osteoblast progenitors, while their antiosteoclastogenic effects are thought to be secondary to impaired osteoblast formation [25].…”
Section: Resultsmentioning
confidence: 99%
“…It looks like bone anabolic activity was at the same rate in both groups of cows. Interestingly, we measured much higher values of bALP in our cows than Filipovi} et al (2008) 14 days before calving and 10 days after calving. Our opinion is that the anabolic effect in our study is due to very high estrogen levels in cows just before calving and estrogen is known to be a osteoprotective anabolic hormone (Riggs et al, 2002).…”
Section: Resultsmentioning
confidence: 47%
“…Some reports of their use in different animal species are published in scientific and professional literature (Allen, 2003). They are already implemented in diagnostic procedures also in dairy cattle (Liesegang et al, 1998;Iwama et al, 2004;Holtenius and Ekelund, 2005;Filipovi} et al 2008;Stari~et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 99%
“…It is very likely that PTHrP expressed by mammary cells exerts a key function in the homeostatic adaptation to lactation in cows. In fact, plasma PTHrP has been shown to increase after parturition in cows (Filipović et al, 2008). Peripheral serotonin has recently been shown to regulate PTHrP gene expression (Hernandez et al, 2012) and, therefore, is involved (through PTHrP) in mammary epithelial cell Ca transport (Laporta et al, 2014).…”
mentioning
confidence: 99%